Answer:
Step-by-step explanation:
Given linear equation as :
3[tex]\sqrt{x}[/tex] - 2 x = - 5
Rearranging the equation
3[tex]\sqrt{x}[/tex] = 2 x - 5
Taking square both side
[tex](3\sqrt{x} )^{2}[/tex] = (2 x - 5)²
Or, 9 x = 4 x² - 20 x + 25 [ from (a + b)² = a² + 2ab + b² ]
Or, 4 x² - 20 x - 9 x + 25 = 0
Or, 4 x² - 29 x + 25 = 0
The equation is in the form of quadratic equation i.e a x² + b x + c = 0
So, x = [tex]\frac{- b\pm \sqrt{b^{2} - 4\times a\times c}}{2\times a}[/tex]
Or, x = [tex]\frac{- (-29)\pm \sqrt{(-29)^{2} - 4\times 4\times 25}}{2\times 4}[/tex]
Or, x = [tex]\frac{- 29\pm \sqrt{841 - 400}}{8}[/tex]
Or, x = [tex]\frac{- 29\pm \sqrt{441}}{8}[/tex]
Or, x = [tex]\frac{-29+21}{8}[/tex] , [tex]\frac{-29-21}{8}[/tex]
Or, x = - 1 , - 6.25
So, The value s of x = - 1 , - 6.25
Hence, The value of x is - 1 , - 6.25 Answer